Necesidad de incorporar en el código orgánico integral penal la responsabilidad penal del empleador por incumplimiento de las medidas de seguridad e higiene. - Vera Ramirez, Carlos Luis (2016)
Daily in our country, we can observe that our workers carry out their jobs in inappropriate and inhuman work environments, which in consequence makes them excessively wear out their energy and in this way become exposed to serious dangers in their physical, psychological and emotional integrity. Due to the high and increasing rate of labor accidents during these past years, it has been my motivation to carry out this thesis, in which the main objective is to compile the existent doctrine, deeply analyze it and study the regulation of this institution in our legislation. Also, the employer‟s responsibility to compensate injured workers do to a task that he or she was accomplishing; and the cases in which the employer is exempted of all responsibilities, will be analyzed. In addition, the compensating fees that the law grants based on the disability of the victim or in other cases, fatal injuries leading to death, will be studied. It has been an arduous and difficult process to finally obtain a legislation of labor accidents; this is why, its‟ continuous evolution is necessary and in this way offer all workers enough confidence in the security systems, so that they can accomplish their tasks in the correct and adequate work conditions.